PENGARUH TAMBAHAN PENGHASILAN TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI PEMERINTAH KABUPATEN SIDOARJO DENGAN PENDEKATAN STRUCTURAL EQUATION MODELING - Munari Kustanto; Fitriyatus Sholihah (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2022)
The government’s performance is largely determined by the performance of its civil servants. The provision of additional income is an effort made by a local government to motivate the performance of civil servants in addition to providing education and training. This study aims to examine the effect of giving TPPD on the performance of civil servants in the Sidoarjo Regency Government. The present research was a survey with a quantitative approach. The population were all PNS receiving TPPD from the Regency Government of Sidoarjo The samples were selected using probability sampling with a random sampling method. The data analysis method was Structural Equation Model (SEM). The results showed that the provision of TPPD had a positive and significant effect on the performance of civil servants in the Sidoarjo Regency Government. Workload has a negative and significant effect on the performance of civil servants. If the Sidoarjo Regency Government wants the performance of civil servants to be more optimal, then the policy of providing TPPD needs to be maintained